2019
DOI: 10.1155/2019/5303869
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Gastrointestinal Heat Retention Syndrome in Children: From Diagnostic Model to Biological Basis

Abstract: Gastrointestinal heat retention syndrome (GHRS) refers to a condition that is associated with increased gastrointestinal heat caused by a metabolic block in energy. It is common in children and is closely related to the occurrence and development of recurrent respiratory tract infection, pneumonia, recurrent functional abdominal pain, etc. However, there are no standardized diagnostic criteria to differentiate the GHRS. Therefore, this study is aimed to establish a diagnostic model for children’s GHRS and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…GHRS is defined by increased gastrointestinal heat with clinical manifestations including fever, sweating, halitosis, thirst and preference for cool drink, dry stool, yellow urine, and tongue redness [ 3 ]. GHRS is induced by intake of a high-calorie and high-fat diet, which mostly occur in children and adolescents, and in more females than males [ 1 ]. Previous clinical studies indicated that core symptoms of GHRS in children were mainly digestive symptoms, inflammatory reactions, and nervous system symptoms, such as dry stool, poor appetite, vomiting, recurrent respiratory tract infections, night restlessness, and irritability [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GHRS is defined by increased gastrointestinal heat with clinical manifestations including fever, sweating, halitosis, thirst and preference for cool drink, dry stool, yellow urine, and tongue redness [ 3 ]. GHRS is induced by intake of a high-calorie and high-fat diet, which mostly occur in children and adolescents, and in more females than males [ 1 ]. Previous clinical studies indicated that core symptoms of GHRS in children were mainly digestive symptoms, inflammatory reactions, and nervous system symptoms, such as dry stool, poor appetite, vomiting, recurrent respiratory tract infections, night restlessness, and irritability [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…GHRS is induced by intake of a high-calorie and high-fat diet, which mostly occur in children and adolescents, and in more females than males [ 1 ]. Previous clinical studies indicated that core symptoms of GHRS in children were mainly digestive symptoms, inflammatory reactions, and nervous system symptoms, such as dry stool, poor appetite, vomiting, recurrent respiratory tract infections, night restlessness, and irritability [ 1 , 5 ]. Realgar, an arsenic tetrasulfide compound, is a highly recognized traditional Chinese medicinal product that has been widely used to treat various diseases such as inflammatory diseases and nervous system injury [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a < 0.5, the item discrimination is not well and can be deleted [ 51 ]; (c) difficulty parameters b. If b > 3, the item difficulty is relatively high and can be deleted [ 52 ]; and (d) considering the discrimination and difficulty of the reserved items comprehensively, the 3 items with the best parameters a and b were selected as the alternative items of the short-form CCMQ.…”
Section: Methodsmentioning
confidence: 99%